In Vivo Imaging of Neutrophil Extracellular Traps (NETs): Visualization Methods and Outcomes. (3rd February 2020) - Alasmari, Sultan Z.
Abstract : Neutrophils comprise the first line of innate immune defense during a host-pathogen interaction. They attack microorganisms directly through three different methods, of which, phagocytosis and degranulation have been known and well-studied for decades. The formation of neutrophil extracellular traps (NETs) is the third and unique method, which was unveiled in 2004. Since then, many studies on NETs have been carried out. However, only few have successfully demonstrated the activity of NETs in vivo . Results of the in vivo studies on NETs have strengthened our understanding of their role in different situations. This review highlights the main in vivo studies, which have contributed in extending our understanding of the role of NETs during infections and diseases, thus indicating their advantages and limitations.